Obesity’s impact on metabolic syndrome clusters andfatty liver incidence in millennial subjects - Achmad, Winnie Pratiwi; Sanusi, Himawan; Parewangi, Andi Muhammad Luthfi; Bakri, Syakib; Iskandar, Harun; Seweng, Arifin (Acta Biomedica Atenei Parmensis, 2024)
Background and Aim:The expanding mass of adipose tissue amplifies the release of free fatty acids, leading to insulin resistance and the onset of metabolic syndrome. In addition to obesity, metabolic syndrome encompasses four other key components. Metabolic Associated Fatty Liver Disease (MAFLD) is a condition characterized by fatty liver occurring in conjunction with metabolic syndrome. However, research into the influence of obesity within metabolic syndrome on the development of fatty liver, particularly in Indonesia, remains limited. This study seeks to elucidate the impact of obesity on the clustering of metabolic syndrome components in millennials and its role in the development of fatty liver. Methods:This cross-sectional study enlisted 91 subjects, subjecting them to screening for metabolic syndrome components and fibroscan examinations to evaluate fatty liver. Statistical analysis encompassed the chi-squared test and multivariate analysis using multiple logistic regression. Results:Among the metabolic syndrome components, obesity emerged as the most significant factor associated with fatty liver (P: 0.002; OR 4.7; 95% CI 1.76–12.70). The obese group with metabolic syndrome exhibited a significantly higher incidence of fatty liver (75.0%; P:< 0.001) compared to the non-obese group (69.8%). In an analysis comparing central obesity with general obesity, it was revealed that general obesity bore a more substantial relationship with the development of fatty liver than central obesity (P:  0.003 vs. 0.102). Conclusions:Obesity represents a substantial risk factor for fatty liver development, especially when combined with metabolic syndrome. Furthermore, general obesity exhibits a more pronounced association with the degree of fatty liver compared to central obesity.